2022
DOI: 10.3390/separations9080199
|View full text |Cite
|
Sign up to set email alerts
|

Using Solid-Phase Microextraction Coupled with Reactive Carbon Fiber Ionization-Mass Spectrometry for the Detection of Aflatoxin B1 from Complex Samples

Abstract: Aflatoxin B1 (AFB1) is a common mycotoxin present in agricultural and food products. Therefore, rapid screening methods must be developed for AFB1 detection with high sensitivity and good selectivity. In this study, we developed an analytical method based on the combination of solid-phase microextraction (SPME) with carbon fiber ionization (CFI)-mass spectrometry (MS) to detect the presence of trace AFB1 from complex samples. A pencil lead (type 2B, length: ~2.5 cm) with a sharp end (diameter: ~150 μm) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…With the emergence of new technologies and novel materials, sample pretreatment methods are also developing. Table S2 [ 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , …”
Section: Sample Pretreatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the emergence of new technologies and novel materials, sample pretreatment methods are also developing. Table S2 [ 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , …”
Section: Sample Pretreatment Methodsmentioning
confidence: 99%
“…However, their sensitivity and selectivity are relatively poor. Recently, the research focus of SPME is new fiber materials, such as graphene- and ILs-based adsorbents [ 55 , 95 ], and novel extraction forms, like in-pipe SPME (IT-SPME) [ 25 ]. Amde et al [ 95 ] synthesized [HMIM][PF6]@ZnO-NRs as the adsorbents of SPME to simply, quickly, and cost-effectively pretreat AFB1, B2, G1 and G2 in food products.…”
Section: Sample Pretreatment Methodsmentioning
confidence: 99%
“…23−27,29−31,35−42 It has been demonstrated that AIMS can be simplified without the need to make any direct electric contact to the ionization emitter when a high voltage is applied to the orifice of the mass spectrometer. [23][24][25][26][27][29][30][31][35][36][37][38][39][40]42 This is because the high electric field provided in the mass spectrometer system is capable of inducing ionization through either electrospray 21,23,25−27,29−31,36−40 or corona discharge. [23][24][25][26]35,42 These approaches are called as field-induced 21 or contactless ionization methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[23][24][25][26]35,42 These approaches are called as field-induced 21 or contactless ionization methods. [23][24][25][26][27][29][30][31][35][36][37][38][39][40]42 For example, when a small piece of insulating fiber 23 or one piece of electric conductive material 25,26,39 was placed close to the metal inlet of the mass spectrometer, which was applied with a high voltage, volatiles or semivolatiles derived from the solid sample deposit on the fiber could be readily ionized and detected by the mass spectrometer. Corona discharge-like processes occur to initiate the ionization of volatiles and semivolatiles derived from the sample, although no direct electric contact was applied on the ionization emitter.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation